Daphnia as a model organism to probe biological responses to nanomaterials—from individual to population effects via adverse outcome pathways - Reilly, Katie; Ellis, Laura-Jayne A.; Davoudi, Hossein Hayat; Supian, Suffeiya; Maia, Marcella T.; Silva, Gabriela H.; Guo, Zhiling; Martinez, Diego Stéfani T.; Lynch, Iseult (Frontiers in Toxicology, 2023)
The importance of the cladoceran Daphnia as a model organism for ecotoxicity testing has been well-established since the 1980s when it was standardised for regulatory testing of chemicals, due to its keystone status and sensitivity to pollutants which make it an essential indicator species. The mapping of the genome of its members D. pulex in 2012 and D. magna in 2017 further consolidated its utility for ecotoxicity testing, including demonstrating the responsiveness of its genome to environmental stressors. Its short lifecycle and parthenogenetic reproduction make it hugely useful for assessment of development toxicity and adaption to stress. The emergence of nanotoxicity assessment has introduced some challenges to use of the standard toxicity tests, developed for soluble chemicals, related to the enormous reactive surface area of nanomaterials, their dynamic interactions with dissolved organic carbon, proteins and other biomolecules in their surroundings and their myriad physical, chemical, biological, and macromolecular transformations. However, the nanomaterials safety assessment are also driving enormous innovations in our approaches to toxicity testing, including driving the development of more realistic environmental exposures via medium composition including pre-conditioning by the organisms, development of microfluidics approaches to mimic flow conditions, utilisation of field daphniids cultured in the lab to assess adaption and impacts of pre-exposure to pollution gradients, and of course development of mechanistic insights to connect the first encounter with nanomaterials to an adverse outcome, via the key events in an adverse outcome pathway. Insights into these developments are presented below to inspire further development and utilisation of this important species alone and as part of an overall aquatic food chain for assessment of nanomaterials impacts including in mixtures.